HUBUNGAN 4C MARKETING 4.0 TERHADAP CUSTOMER LOYALTY DENGAN MEDIASI CUSTOMER JOURNEY DAN MODERASI USER INTERFACE (Study Kasus Pada Pelanggan Pengguna OTA Pegi-Pegi di Kab. Bekasi) - Bintarti, Surya; Ramadhaniah, Indah (ITB AAS Indonesia Surakarta, 2024)
This research examines the influence of co-creation, currency, communal activation, and conversation on the consumer journey at Pegipegi. Apart from that, it also examines whether these factors influence customer loyalty with the customer journey as a mediator. Next, this research examines whether these factors also influence customer loyalty with the customer journey as a mediator, and the user interface as a moderator. The sampling method used was purposive sampling with 104 respondents aged 17-45 years in Bekasi Regency. Data were analyzed using Structural Equation Model (SEM) through the SmartPLS 3.0 program to test the validity and reliability of the instrument, evaluate model suitability, and explore relationships within the proposed theoretical framework